Expression of adrenergic, acetylcholine and kappa opioid receptors on peripheral blood lymphocytes in patients with herpetic keratitis and those with idiopathic anterior and/or intermediate uveitis (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To assess the expression of adrenergic, acetylcholine (ACh) and opioid receptors on peripheral blood lymphocytes in patients with herpetic keratitis (HK) and those with idiopathic anterior and/or intermediate uveitis (IAIU).Methods: Thirty one patients with HK (group 1; age, 40.7 ± 14.2 years), 36 patients with IAIU (group 2; age, 49.9 ± 12.5 years), and 12 healthy volunteers (controls; age, 43.5 ± 14.8 years) were included in the study and examined at Immunology laboratory, SI “The Filatov Institute of Eye Diseases and Tissue Therapy of the NAMS of Ukraine”. Immunocytochemistry with monoclonal antibodies to receptors and fluorescein microscopy were used. IBM SPSS Statistics software and spreadsheets were used for the statistical analysis.Results: Expression of β adrenergic receptors, Ach receptors and kappa opioid receptors (KOR) on lymphocytes was significantly increased in patients with HK and patients with IAIU compared to healthy controls. There was a significant difference in the ratio of expression of β adrenergic receptors to KOR on peripheral blood lymphocytes (expressed as percentage) between patients with HK and healthy controls and between patients with IAIU and healthy controls.
Keywords: uveitis; herpetic keratitis; opioid receptors; β2 adrenergic receptors; cornea